Analysis of Prohibited and Restricted Ingredients in Cosmetics - Rimadani Pratiwi; Nisa Nurul Auliya As; Rani Fitrilia Yusar; Adnan Aly Al Shofwan (Cosmetics, 2022)
The general public uses cosmetics daily. Cosmetic products contain substances (ingredients) with various functions, from skincare to enhancing appearance, as well as ingredients that preserve the cosmetic products. Some cosmetic ingredients are prohibited or restricted in certain geographical regions, such as the European Union and the United States of America, due to their potential to cause adverse effects such as cancer, birth defects, and/or developmental and reproductive disorders. However, the ingredients may be used in other regions, and, hence, the monitoring of the cosmetic ingredients actually used is important to ensure the safety of cosmetic products. This review provides an overview of recent analytical methods that have been developed for detecting certain ingredients that are restricted or prohibited by the U.S. Food and Drug Administration (FDA) and/or EU legislation on cosmetic products.